PELATIHAN MENGHITUNG HPP PADA PELAKU UMKM KUE SUKADE DI DESA KOPI - GITA JUNIARTI (Sawala : Jurnal pengabdian Masyarakat Pembangunan Sosial, Desa dan Masyarakat, 2023)
The objective of community development activity at Desa Kopi, North Bulango District, Bone Bolango Regency is to provide the MSME business owners a set of knowledge about calculating production cost of goods and services. The calculation result can later be used to determine how much the selling price of the final product will be. The commodity in Desa Kopi is palm plantation, so palm-based products become one of the businesses developed by local community in Desa Kopi. One of the palm-based products is Sukade cake which is a traditional food from Gorontalo Province. Sukade cakes were made as daily meals. Some local MSME business owners only distribute it at nearby stalls and traditional markets. Therefore, this project is expected to help locals to sell the cake with more suitable price, so that MSME business owners are able to gain more profit. The project was held from July to September 2022 targeting on the local Sukade cake business owners. The preparation started with observation and interviews, training on Cost of Good Sold (HPP) analysis, and final evaluation through interviews with MSME business owners. This project effectively provided MSME business owners with the desired knowledge on the HPP specifically on Sukade cake.